Peningkatan Keterampilan Motorik Kasar Melalui Tari Gugur Gunung pada Anak Usia 4-5 Tahun di RA Ar Rafif Kecamatan Kalasan - Vera Oktafia; Uswatur Rohmah; Uswatun Hasanah; Vera Yuliyani; Vera Siti Magfiroh (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This research aims to improve gross motor skills through the "Gugur Gunung Dance" in the RA A group with children aged 4-5 years at RA Ar Rafif, Tirtomartani, Kalasan, Sleman, D.I Yogyakarta. The motor skills examined in this research include flexibility, agility and balance. This research uses a type of classroom action research. Using the Kemmis and Mc model. Taggart goes through several flows such as planning, implementation, observation and reflection. The subjects of this research were girls from the RA A group from Makkah and Arafah classes with children aged 4 to 5 years with a total of 14 children. The results of increasing gross motor skills in the pre-action stage were 44.64%, then increased after action in cycle I to 53.57% with an increase of 8.93% then in cycle II to 84.52%, an increase from cycle I of 30.95% so that the percentage increase in children's gross motor skills has exceeded the target indicator of success.